Pengaruh Healing of Magic Terhadap Tingkat Kecemasan Masyarakat Desa Manggihan Kabupaten Semarang Jawa Tengah - Susanto, Wigyo; Sejati, Waluyo; Setyowati, Wahyu Endang; Rochmawati, Dwi Heppy; Febriana, Betty (Jurnal Keperawatan Komplementer Holistic, 2025)
Excessive anxiety is one of the reasons a person can become sick (stressed), can tantrum, and can lock himself up. In order to stay relaxed and relaxed a person needs adaptive coping. Magic games have been used as a therapeutic method in rehabilitation settings since 1982 in America, and have received strong recognition as an effective method for treating anxiety in patients (Healing of magic). With the provision of healing of magic, it is hoped that the patient's anxiety can be resolved properly. This study aims to measure the level of anxiety of the residents of the Manggihan village affected by COVID-19 before and after being given an intervention in the form of Healing of magic therapy (magic therapy). The study was conducted on 18 respondents by giving a Hamilton Rating Scale for Anxiety (HRS-A) questionnaire before and after therapy. The questionnaire was then analyzed using the marginal homogeneity test, and the p value results showed the number .003, which means that there is a significant difference between the level of anxiety before therapy and the level of anxiety after therapy. So it can be concluded that healing of magic therapy is very effective in reducing anxiety levels.